Literature Review: Alkaloid Compounds in Medicinal Plants: Mechanisms and Anti-Diabetic Potential - Rahmadhani, Ade Novira; Rismawati, Lia; Nurramadhani, Aisyah Zahra; Syahputri, Salsabila Dia; Saputri, Rindiani Dwi; Usman, Usman (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Alkaloids are a group of chemical compounds found in nature with the most basic nitrogen atoms. As many as 20% of plant species contain alkaloid compounds, one of which is flowering plants. Plants that contain alkaloid compounds have the potential to be antidiabetic agents. This literature review research uses the narrative literature review method. Using keywords from the range of 2014-2024, a total of 25 articles were obtained. Diabetes is a common metabolic disease caused by insulin deficiency. The plants that contain bioactive alkaloid compounds are Catharanthus roseus, Portulaca oleracea L. (PO), Momordica charantia (Bitter Melon), Uncaria Nervosa Elmer (Bajakah), Peperomia Pelucida (Water Pepper), Mulberry, Ageratum conyzoides L (Ageratum), Syzygium sp (Red Pakoba Fruit), Sansevieria trifasciata (Mother-in-law's Tongue), Triumfetta cordifolia, Phrynium Capitatum (Rice Leaf), and Annona Muricata L. (Soursop Leaf), which have been proven to contain alkaloid activity compounds that can be used as anti-diabetic agents. Alkaloid compounds play an essential role in diabetes management through various mechanisms that regulate blood glucose levels.